"Once Upon A Star": A Science Education Program Based on Personification Storytelling in Promoting Preschool Children's Understanding of Astronomy Concepts. Issue 1 (2nd January 2021) - Hu, Jiangbo; Gordon, Camilla; Yang, Ning; Ren, Yonggang
ABSTRACT: Research Findings: Grounded on personification storytelling, this intervention study introduced a science program including extensive astronomy concepts to 24 children (4–5 years). The storytelling attributes personal characteristics to cosmic bodies with metaphors relating to children's lives in explaining the scientific concepts, for example, the star explosion is presented as "a big vomit." Drawing on such storytelling combined with follow up hands-on activities and free drawing, the children showed significant improvement in their understanding of the astronomy concepts. The children's understanding was assessed with means of triangulation, including the analysis on pre- and post-intervention interviews, educators' documentations, and children's work samples. The analysis was based on Vygotsky's sociocultural notion of children's development of understanding from everyday concepts to scientific concepts. This study demonstrates preschool children's potential in understanding abstract astronomy concepts that were considered unsuitable to them. Practice or Policy : The pedagogical function of storytelling in science education is widely recognized, yet its application is impaired by the fact that writing stories is difficult. The personification storytelling would inspire the story writing employing the similar strategies for the promotion of science education. This study confirms the claim that preschool children are capable of developing conceptual understanding in "real astronomy."